Think FAST: Applying citizen science to survey the ecological status of fish assemblages in the Côte d’Azur - BEBER, ISAAC; LACROSSE, FLORENCE; FRANCOUR, PATRICE; ELOIRE, DAMIEN; JEGLOT, SAMUEL (Mediterranean Marine Science, 2025)
Fish assemblages are vital for the functioning of Mediterranean coastal ecosystems, yet they have long been overexploited by recreational and professional fishing. In response to this overexploitation, No-take Zones (NTZs) have been applied, resulting in significant conservation benefits. This study, conducted by citizen scientists and members of the scientific community in the north-western (NW) Mediterranean Sea, investigated spatial trends in fish assemblages targeted by small scale and recreational fisheries using the Fish Assemblage Survey Technique (FAST). A total of 1356 fifteen-minute replicate counts, corresponding to 452 hours in the water over a six-year period (2018 – 2023) were analyzed. Results indicated that the ecological status of fish assemblages were spatially dependent, where poor fish assemblage health was observed at dive sites situated in the Lérins Islands, highlighting an area of conservation priority. NTZs were associated with a higher presence of small (p < 0.001) and large (p <0.001) size classes of Serranidae fishes. They were also associated with a higher presence of large, threatened carnivorous species: Dentex dentex (p < 0.001), Epinephelus marginatus (p < 0.001), and Sciaena umbra (p < 0.001). Results from this study suggested that data collected by citizen scientists using FAST was robust enough to meet the same conclusions as researchers. We conclude on the positive application of citizen science programs to assess the ecological status of fish assemblages; fill the need for simple, effective monitoring in Marine Protected Areas (MPAs) and understudied areas; and inform conservation policies focused on threatened habitats and associated marine biodiversity in the French region Provence-Alpes-Côte d’Azur (PACA).